El síndrome de asperger y su incidencia en el desarrollo socio-afectivo de niños de 5 años de edad del centro especializado en atención psicológica y psicopedagógica de la ciudad de Guayaquil - Mendoza Bajaña, Viviana Paola (2015)
People with Asperger’s syndrome have different cognitive styles. Their way of thinking is very logical, precise and imaginative. The disabilities that are not usually very obvious, is achieved to express levels of inappropriate social behaviors, this provides them and their family members difficulties in all areas….